Optimized persistent neural network for EEG-based predilection cataloguing in neurobased-marketing - Patil, Shashikant (AIP Conference Proceedings, 2025)
General brain-computer interface (BCI) concepts make use of brain response to visual stimulus to recognize the user’s anticipated target to control the device. A lot of BCI concept and decoding schemes do not focus on the basic functioning of brain responses and sensory pathways directly. This research aims at bridging the gap among conventional market research that relies upon customer responses. In this work, optimized RNN is espoused to perceive the buyer predilections by means of EEG signs (DEAP dataset). The proposed work follows three major segments: “Data pre-processing, relevant feature abstraction and predilection recognition”. On paramount, the EEG indication is endangered to pre-processing via Gaussian filtering. Subsequently, the features like entropy, Power spectral density (PSD), and DWT based signals are mined from the earlier-processed indication. Finally, the preference classification is carried out by optimized RNN, where the training is carried out by a new “Elephant Herding with Adaptive Cauchy’s Mutation (EH-ACM)” via tuning the optimal weights. The model differentiates the pleasant and unpleasant preferences. The recital of projected drudgery is equated over other representations with respect to mottled metrics.
uGDX